2018
DOI: 10.3847/1538-4365/aac833
|View full text |Cite
|
Sign up to set email alerts
|

A Light Curve Analysis of Recurrent and Very Fast Novae in Our Galaxy, Magellanic Clouds, and M31

Abstract: We analyzed optical, UV, and X-ray light curves of 14 recurrent and very fast novae in our galaxy, Magellanic Clouds, and M31, and obtained their distances and white dwarf (WD) masses. Among the 14 novae, we found that eight novae host very massive ( 1.35 M ⊙ ) WDs and are candidates of Type Ia supernova (SN Ia) progenitors. We confirmed that the same timescaling law and timestretching method as in galactic novae can be applied to extra-galactic fast novae. We classify the four novae, V745 Sco, T CrB, V838 Her… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
50
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 163 publications
(433 reference statements)
6
50
0
Order By: Relevance
“…Applying the obtained f s and ∆V to Equation (4), we have the relation of Thus, we obtain (m − M ) V = 11.86 ± 0.1 for LV Vul, being consistent with our previous results of (m−M ) V = 11.85 ± 0.1 (Hachisu & Kato 2018b).…”
Section: Vul 1968#1supporting
confidence: 90%
See 2 more Smart Citations
“…Applying the obtained f s and ∆V to Equation (4), we have the relation of Thus, we obtain (m − M ) V = 11.86 ± 0.1 for LV Vul, being consistent with our previous results of (m−M ) V = 11.85 ± 0.1 (Hachisu & Kato 2018b).…”
Section: Vul 1968#1supporting
confidence: 90%
“…By directly fitting the theoretical light curves of M V with the observed m V , we can also estimate the WD mass M WD and distance modulus in the V band of µ V ≡ (m − M ) V for a target nova. Hachisu & Kato (2018b) confirmed that the time-stretching method is applicable to fast and very fast novae in our Galaxy, LMC, and M31.…”
Section: Introductionsupporting
confidence: 77%
See 1 more Smart Citation
“…Figure 3(a) shows the light curve of U Sco in the 2010 outburst. We adopt the distance modulus in the V band to be (m − M ) V = 16.3 (Hachisu & Kato 2018b). Around the optical peak, the brightness is dominated by the emission from the ejecta.…”
Section: U Scomentioning
confidence: 99%
“…1) to the collision between the slowly expanding torus with the faster nova wind, which is consistent with the model proposed byLi et al (2017).4. According toHachisu & Kato (2018), the slow decline of the optical flux F ∝ t −1 , observed for some novae during the early stage of their evolution, can be caused by the shock interaction that decelerates the ejecta resulting in a slower decrease of its den-…”
mentioning
confidence: 99%